2015
DOI: 10.2131/jts.40.685
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis in the lung of the rasH2 transgenic mouse at week 4 prior to induction of malignant tumor formation by urethane and N-methylolacrylamide

Abstract: -The rasH2 transgenic (Tg) mice are susceptible to genotoxic and some non-genotoxic carcinogens. In carcinogenicity studies carried out using rasH2 Tg mice, the carcinogenic potential of chemicals are evaluated over a 26-week experimental period. In the present study, we examined the comprehensive gene expressions in the lungs of Tg and non-Tg mice prior to the induction of malignant tumors. Urethane (UR), a mutagenic carcinogen, was administered for 4 weeks, and thereafter withdrawn for 22 weeks. N-methylolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Even when the knees of mice genetically modified to develop cancer spontaneously (i.e., rasH2 mice) were injected with large amounts of MWCNTs under severe conditions as we did with the aforementioned rats, no cancer developed. With regard to this test in rasH2 mice, the US, EU, and Japanese regulatory authorities have already issued guidelines for accepting chemical substances data submitted as carcinogenicity study data. , More than one study has reported on bulk biomaterials . However, our study of MWCNTs implanted in subcutaneous tissue is the only published report on nanoparticle biomaterials such as MWCNTs to show that MWCNTs are not carcinogenic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the knees of mice genetically modified to develop cancer spontaneously (i.e., rasH2 mice) were injected with large amounts of MWCNTs under severe conditions as we did with the aforementioned rats, no cancer developed. With regard to this test in rasH2 mice, the US, EU, and Japanese regulatory authorities have already issued guidelines for accepting chemical substances data submitted as carcinogenicity study data. , More than one study has reported on bulk biomaterials . However, our study of MWCNTs implanted in subcutaneous tissue is the only published report on nanoparticle biomaterials such as MWCNTs to show that MWCNTs are not carcinogenic .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to this test in rasH2 mice, the US, EU, and Japanese regulatory authorities have already issued guidelines for accepting chemical substances data submitted as carcinogenicity study data. 41,42 More than one study has reported on bulk biomaterials. 43 However, our study of MWCNTs implanted in subcutaneous tissue is the only published report on nanoparticle biomaterials such as MWCNTs to show that MWCNTs are not carcinogenic.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Some environmental carcinogens have also been shown to induce EREG expression in the lungs. EREG expression was increased in lung tumors induced by the environmental carcinogen of urethane in a murine experimental model [46]. Recently, Chen et al [47] demonstrated that long-term exposure to 3-nitrobenzanthrone, which is a carcinogen in diesel exhaust, promotes malignant transformation in human bronchial epithelial cells through the EREG-mediated activation of the MEK/ERK and PI3K/AKT pathways.…”
Section: Physiological Role Of Ereg In Human Airway Epithelial Cellsmentioning
confidence: 98%